An Overview of Global Efforts Towards AI Regulation - Davtyan, Tatevik (Bulletin of Yerevan University C: Jurisprudence, 2024)
This article provides a global perspective on the efforts to regulate artificial intelligence (AI), a transformative force reshaping businesses, governments, and societies globally. It examines the different approaches various countries and international organizations take in response to the rapid advancements in AI technologies. As AI continues to transform, there is a growing need for comprehensive regulatory frameworks to address its complex ethical, social, and economic challenges. The article presents the AI regulatory strategies of key jurisdictions, including the U.S., UK, Canada, China, Japan, Singapore, Israel, India, and the European Union, influenced by their unique political, economic, and cultural contexts. It also explores the initiatives of international and intergovernmental organizations such as the United Nations, Council of Europe, G7, and OECD in establishing global standards and guidelines for AI’s ethical and responsible use. This overview is a valuable resource for understanding the evolving landscape of AI governance. It provides a foundation for further research and policy development to balance innovation with protecting public interests, upholding human rights, and mitigating potential risks.